Depositional environment of the Late Santonian lacustrine source rocks in the Songliao Basin (NE China): Implications from organic geochemical analyses. (October 2018) - Tong, Xiaoning; Hu, Jianfang; Xi, Dangpeng; Zhu, Mengbo; Song, Jianzhong; Peng, Ping'an
Highlights: OM deposited in a stratified water column with an episodic anoxic photic zone. Seawater incursions are correlated with deposition of organic-rich source rocks. The water column ranged in salinity from semi-brackish to brackish. Abstract: The Songliao Basin (SLB) located in northeastern China is one of the largest Cretaceous continental sedimentary basins in the world. The SLB is filled with sediments deposited in the Upper Jurassic, the Lower Cretaceous and the Upper Cretaceous epochs. The Nenjiang Formation (K2 n) is subdivided into five members, where Member 2 (K2 n 2 ) was deposited in the late Santonian in the lower part of the Nenjiang Formation. This member is characterized by a thick succession of organic-rich source rocks. However, the complexity of the depositional environment raises questions about the specific factors that drove this accumulation of organic material. Here, we present data on the total organic carbon (TOC) contents and their stable carbon isotope values (δ 13 Corg ), as well as biomarker data from 50 outcrop samples collected from the Yuewangcheng (YWC) section, in the southeastern SLB. According to the variations of the bulk organic parameters (TOC and δ 13 Corg ) and biomarker indices, the profile could be divided into three stages (stages I–III). The distribution of biomarkers ( n -alkanes, steranes and hopanes) and δ 13 Corg values indicate that the organic matter (OM) in the Lower K2 n 2 is derived largely from algae and macrophytes, with a minor input from bacteria and land plants. The water column was stratified, as indicated by the presence of gammacerane. Variations in the pristane/phytane (Pr/Ph) and aryl isoprenoids relative to phenanthrene ratio (A-i/P) suggest that bottom waters were anoxic during Stage I (31.5–26.0 m) and Stage II (26.0–16.3 m), with the anoxic layer impinging on the euphotic zone and a relative oxic environment at Stage III (16.3–0 m). This brackish environment persisted in the water over the interval represented by the section, as reflected by methytrimethyltridecyl chromans (MTTCs) Index (MTTCI) and α-MTTC/γ-MTTC ratios. Marine transgressions, with subsequent seawater incursions, can be detected with the presence of 24- n -propyl-cholestanes and 24-isopropyl-cholestanes in the Lower K2 n 2 sediments, especially during Stage I. These seawater incursions are closely correlated with anoxic conditions and the deposition of organic-rich source rocks.